1999
DOI: 10.1007/s002329900598
|View full text |Cite
|
Sign up to set email alerts
|

Ion Permeation and Block of P2X 2 Purinoceptors: Single Channel Recordings

Abstract: P2X(2) purinoceptors are cation-selective channels activated by ATP and its analogues. Using single channel measurements we studied the channel's selectivity for the alkali metal ions and organic monovalent cations NMDG(+), Tris(+), TMA(+), and TEA(+). The selectivity sequence for currents carried by alkali metal ions is: K(+) > Rb(+) > Cs(+) > Na(+) > Li(+), which is Eisenman sequence IV. This is different from the mobility sequence of the ions in free solution suggesting there is weak interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 39 publications
13
53
0
Order By: Relevance
“…However, the distance between Thr-336 residues of open channels, if they are at the gate as our data and the model suggests (see below and Fig. 7), is expected to be greater than 8 Å, which is the minimal open pore diameter based on ion replacement studies (11,61,(65)(66)(67)(68)(69). Thus, we believe Cd 2ϩ is not tightly bound at T336C and most other TM2 hits because the number of available cysteines and the distance between them is not optimal for coordination.…”
Section: ϩsupporting
confidence: 49%
“…However, the distance between Thr-336 residues of open channels, if they are at the gate as our data and the model suggests (see below and Fig. 7), is expected to be greater than 8 Å, which is the minimal open pore diameter based on ion replacement studies (11,61,(65)(66)(67)(68)(69). Thus, we believe Cd 2ϩ is not tightly bound at T336C and most other TM2 hits because the number of available cysteines and the distance between them is not optimal for coordination.…”
Section: ϩsupporting
confidence: 49%
“…The concentration-dependence of P2XR activation measured by whole-cell (Bean et al, 1990;Jiang et al, 2003) and single-cell (Ding and Sachs, 1999) recording suggested that three molecules of ATP were required for channel gating. Biochemical studies showed that under nondenaturizing conditions, P2XRs migrated as trimers in polyacrylamide gel electrophoresis, therefore suggesting that this was the conformation of native functional channels (Nicke et al, 1998).…”
Section: Molecular and Crystal Structure Of P2x2 Receptorsmentioning
confidence: 99%
“…This was based on the superlinearity of currents versus agonist concentration observed at low ATP concentrations (Bean et al, 1990). Single-channel experiments also suggested that the binding of three ATP molecules was required to activate the P2X2R (Ding and Sachs, 1999). However, other reports have suggested that the binding of two (Friel and Bean, 1988;Friel, 1988) or even one molecule of ATP (Krishtal et al, 1983) is sufficient to activate channels.…”
Section: Number Of Occupied Binding Sites Necessary To Channel Activamentioning
confidence: 99%
“…P2XRs conduct Ca 2ϩ and Mg 2ϩ (14,21,30), but these metals can also inhibit those receptors at millimolar concentrations (5,13,30,38). This raised the possibility that these Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The macroelements Ca 2ϩ and Mg 2ϩ also have a modulatory role on P2XRs; their main effect in a millimolar concentration range is inhibition of agonist-induced currents (30), but there is also evidence suggesting a positive effect of Ca 2ϩ in recovery from desensitization of P2X3Rs (8). In cells expressing P2X2R, an inhibitory effect of Ca 2ϩ and Mg 2ϩ has also been detected with single-channel recording as a reduction of unitary currents (13). The same group also observed Ca 2ϩ -dependent receptor desensitization although the mechanism of its action was not determined (12).…”
mentioning
confidence: 97%